Pengembangan Prototype Media Game Wordwall dalam Menanamkan Perilaku Hidup Bersih Pada Anak Usia Dini di TK Permata Sunnah Kecamatan Kota Selatan Kota Gorontalo - Syarifah Syarifah; Pupung Puspa Ardini; Nurhayati Tine (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The lack of learning media for early childhood that motivates children to practice clean living behavior in school is the main issue addressed in this study. This research aims to develop a Wordwall game media prototype to instill clean living behavior in Group B Children at TK Permata Sunnah Kindergarten, Kota Selatan District, Gorontalo City. The research utilized a development method, specifically Research and Development (R&D), following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) proposed by Sugiyono (Aini et al., 2023). The study’s findings reveal that the Wordwall game media is highly feasible for instilling clean living behavior, as indicated by the result of expert validation tests. The material expert validation scored 87,27% (very feasible), and the media expert validation scored 96,67% (very feasible). Additionally, pilot tests with teachers showed a feasible percentage of 88,57% (very feasible), while testing with children yielded a score of 4 (feasible). Finally, usage trials with teachers resulted in a feasibility percentage of 97,14% (very feasible), and large-group testing with children scored 5 (very feasible). The study concludes that the development of the Wordwall game media prototype effectively instills clean living behavior in children..